New catalytic designs of Pt on carbon nanotube-nickel-carbon black for enhancement of methanol and formic acid oxidation - Suwaphid Themsirimongkon (2020)
© 2020 Elsevier B.V. The synthesized nickel (Ni) nanoparticles are attached on mixed carbon support multi-walled carbon nanotubes (CNT) and carbon black (CB) as a composite support before loading with Pt nanoparticles, and various carbon compositions of Pt/xCNT-Ni-yCB catalyst materials (x and y = 1–2) were prepared. The as-prepared catalysts were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and their electro-characteristics, activity and stability were determined via electrochemical measurements. The results demonstrate that Pt/1CNT-Ni-2CB shows higher catalytic activity, electron transfer and stability than other catalysts (e.g., Pt/1CNT-Ni-1CB and Pt/2CNT-Ni-1CB) and commercial Pt/C towards oxidizing methanol and formic acid. The architecture of the mixed CNT and CB carbon structure induces unique structural and functional properties of those catalyst components and remarkably enhances electrochemical activation and catalytic performance. Thereby, demonstrating a synergistic effect between these components, which is also discussed in this article.